HnRNP A1 antagonizes cellular senescence and senescence‐associated secretory phenotype via regulation of SIRT1 mRNA stability. Issue 6 (9th September 2016) - Wang, Hui; Han, Limin; Zhao, Ganye; Shen, Hong; Wang, Pengfeng; Sun, Zhaomeng; Xu, Chenzhong; Su, Yuanyuan; Li, Guodong; Tong, Tanjun; Chen, Jun
Summary: Senescent cells display a senescence‐associated secretory phenotype (SASP) which contributes to tumor suppression, aging, and cancer. However, the underlying mechanisms for SASP regulation are not fully elucidated. SIRT1, a nicotinamide adenosine dinucleotide‐dependent deacetylase, plays multiple roles in metabolism, inflammatory response, and longevity, etc. However, its posttranscriptional regulation and its roles in cellular senescence and SASP regulation are still elusive. Here, we identify the RNA‐binding protein hnRNP A1 as a posttranscriptional regulator of SIRT1, as well as cell senescence and SASP regulator. hnRNP A1 directly interacts with the 3′ untranslated region of SIRT1 mRNA, promotes its stability, and increases SIRT1 expression. hnRNP A1 delays replicative cellular senescence and prevents from Ras OIS via upregulation of SIRT1 expression to deacetylate NF‐κB, thus blunting its transcriptional activity and subsequent IL‐6/IL‐8 induction. hnRNP A1 overexpression promotes cell transformation and tumorigenesis in a SIRT1‐dependent manner. Together, our findings unveil a novel posttranscriptional regulation of SIRT1 by hnRNP A1 and uncover a critical role of hnRNP A1‐SIRT1–NF‐κB pathway in regulating cellular senescence and SASP expression.